Influence of Sperm Number and Antioxidant Melatonin in Extender on the Quality of Post-Thawing Sheep Spermatozoa - Frilianty Putri; Ni Wayan Kurniani Karja; Mohamad Agus Setiadi; Ekayanti Muyawati Kaiin (Indonesian Center for Animal Research and Development (ICARD), 2023)
This study aimed to examine the effect of spermatozoa concentration and the effectiveness of melatonin supplementation in diluent on the quality of post-thawing semen. Ejaculated semen was collected using the artificial vaginal method (MVB). The study was carried out in two stages, firstly semen was frozen in andromed diluent with different concentrations in one straw (50, 100, 200 million per straw), and the second was frozen semen in diluent supplemented with melatonin with different doses (0, 0,5, 1, 0 and 1.5 mM melatonin). Parameters observed were the movement of spermatozoa using Computer Assisted Sperm Analysis, membrane integrity, and acrosome integrity. Data were analyzed using ANOVA and further tested using Duncan's test. The results showed no significant difference in the quality and movement pattern of sheep semen when frozen at concentrations of 50, 100, or 200 million per straw (P 0.05). Furthermore, adding melatonin to the diluent in this study affected spermatozoa's total motility and progressive motility at a concentration of 1.0 mM (P0.05) but did not significantly affect the percentage of spermatozoa motility pattern characteristics. From the results, it can be concluded that the concentration of per straw spermatozoa does not affect the quality of sheep semen, and melatonin supplementation in diluent can reduce the effects of the frozen-thawed process on motility, acrosome cap, and plasma membrane integrity in sheep semen. Melatonin supplementation with a concentration of 1 mM in the extender was the highest quality concentration in this study.